2021
DOI: 10.1530/ec-20-0589
|View full text |Cite
|
Sign up to set email alerts
|

RET mutated C-cells proliferate more rapidly than non-mutated neoplastic cells

Abstract: A statistically significant higher prevalence of the RET p.Met918Thr somatic mutation, identified by direct sequencing, was previously reported in MTC >2 cm than in smaller tumors. Aim of this study was to correlate the full RET and RAS mutation profile, identified by a Next Generation Sequencing approach, with the growth rate, proliferation and tumor size of MTC. Data of 149 sporadic MTC patients were correlated with RET mutations and Ki67 positivity. Eighty-one cases had a somatic RET mutation, 40 a RAS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…As reported by Le Hiret al [16] it is likely that, in tumors caused by RET mutations, the presence of higher amounts of the long isoform can confer a selective growth advantage as demonstrated by the evidence that, in PC12 cells, the RET51 isoform displays a more prominent potential as compared to the corresponding RET9 isoforms [31,34]. This is in line with our previous evidence that sporadic MTC cases with a RET somatic mutation show a more rapid growth rate with respect to not-mutated cases in which RET51 isoform is less expressed [29].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As reported by Le Hiret al [16] it is likely that, in tumors caused by RET mutations, the presence of higher amounts of the long isoform can confer a selective growth advantage as demonstrated by the evidence that, in PC12 cells, the RET51 isoform displays a more prominent potential as compared to the corresponding RET9 isoforms [31,34]. This is in line with our previous evidence that sporadic MTC cases with a RET somatic mutation show a more rapid growth rate with respect to not-mutated cases in which RET51 isoform is less expressed [29].…”
Section: Discussionsupporting
confidence: 88%
“…These findings indicate that the increased rate of RET transcription and its higher expression cannot be considered as causative in RET− and RAS− cases. We recently demonstrated [29] that the prevalence of RET somatic mutations is higher in MTC of a larger tumor size, suggesting that the presence of this genetic alteration can induce a higher cell proliferation rate. According to these data, RET-mutated MTC cells could have a more active metabolic condition, thus also justifying higher levels of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant result of our study has been the evidence that the AF of the driver mutation detected in the tumoral tissue DNA was significantly higher in cases where the same mutation was detected in the pre-operative ctDNA respect to those that had a negative pre-operative ctDNA. We previously demonstrated that MTC with a higher RET mutation AF are usually bigger and have a higher growth rate (24) and this may be the cause of the release in the blood of a greater number of tumoral cells and/or DNA, that are responsible of the ctDNA detection, already before surgery. When we compared the positivity of pre-operative ctDNA with serum levels of Ct and CEA, we observed that both biomarkers, but mainly CEA, levels were higher in those cases presenting a positive pre-operative ctDNA.…”
Section: Association Between Ctdna Detection and Serum Ct And Cea Levelsmentioning
confidence: 99%